Perilaku Manajemen Laba Perusahaan Dan Konservatisma Akuntansi: Berbeda Atau Sama? - Lodovicus Lasdi (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2008)
Academics said that earnings management and conservatism literatures are two different topics. Conservative accounting is different from earnings management in earnings determination. However, other academics claim that it is difficult to differentiate earnings management from conservatism in accounting. Both concepts have the same idea that manager can use their judgement to influence financial reporting, that is discretionary accrual. The purpose of this article is bridging this two stream by looking interaction between earnings management and conservatism in accounting.